2014
DOI: 10.1177/0300060514549781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhalational anaesthetic on postoperative cognitive dysfunction following radical rectal resection in elderly patients with mild cognitive impairment

Abstract: Aims: To determine the effect of choice of inhalational anaesthetic (sevoflurane vs propofol) on the incidence and severity of postoperative cognitive dysfunction (POCD) in elderly patients (aged ! 60 years) with mild cognitive impairment (MCI). Methods: Elderly patients with MCI undergoing radical rectal resection were randomly assigned to receive sevoflurane or propofol general anaesthesia. Cognitive function was assessed using neuropsychological testing before and 7 days after surgery. POCD severity was gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 26 publications
1
57
0
2
Order By: Relevance
“…One recent study found increased rates of MCI progression two years later in spine surgery patients who were randomized to receive sevoflurane vs propofol or epidural anesthesia (N=60 per group, (63)). Another study among MCI patients found no difference in POCD rates among MCI patients randomized to receive sevoflurane (N=99) vs propofol anesthesia (N=101) for radical rectal resection, although there was an increased rate of severe POCD in the sevoflurane treated patients (64). Taken together, these studies raise the possibility that propofol anesthesia (as compared to sevoflurane anesthesia) might be associated with improved post-operative cognition in patients with MCI, but further studies are necessary to examine this issue.…”
Section: Who Is At Risk For Developing Pocd?mentioning
confidence: 99%
“…One recent study found increased rates of MCI progression two years later in spine surgery patients who were randomized to receive sevoflurane vs propofol or epidural anesthesia (N=60 per group, (63)). Another study among MCI patients found no difference in POCD rates among MCI patients randomized to receive sevoflurane (N=99) vs propofol anesthesia (N=101) for radical rectal resection, although there was an increased rate of severe POCD in the sevoflurane treated patients (64). Taken together, these studies raise the possibility that propofol anesthesia (as compared to sevoflurane anesthesia) might be associated with improved post-operative cognition in patients with MCI, but further studies are necessary to examine this issue.…”
Section: Who Is At Risk For Developing Pocd?mentioning
confidence: 99%
“…16e19 Other studies have found no significant differences with respect to cognitive outcomes between propofol and sevoflurane anaesthesia. 20,21 In contrast, yet another study found better cognitive outcome after sevoflurane than after propofol anaesthesia in patients with impaired cerebral oxygenation. 22 The reasons behind these conflicting findings are unknown.…”
mentioning
confidence: 96%
“…30 In contrast, a prospective randomized parallel-group study comparing propofol, sevoflurane, and epidural anaesthesia found that the sevoflurane group had a greater progression to amnestic mild cognitive impairment at 2 yr. 31 Likewise, elderly patients receiving sevoflurane for rectal surgery had a significantly higher severity of POCD compared with propofol. 32 In a small study of patients having endoscopic sinus surgery including lumbar drains, postoperative cerebrospinal fluid IL-6 was higher in the group that received sevoflurane compared with propofol and remifentanil. 33 Furthermore, reduced gene expression of pro-inflammatory cytokines was found with propofol anaesthesia in humans, 34 and in a recent study of 90 patients undergoing major non-cardiac surgery, sevoflurane was associated with greater POCD and inflammation (IL-6 and tumour necrosis factor-a) than propofol.…”
Section: Discussionmentioning
confidence: 96%